Estudos sobre avaliação da função muscular inspiratória e da capacidade funcional - Dayane Montemezzo (2015)
The rehabilitation sciences has been using tools and procedures feasible and valid for the management of functional outcomes both, in clinical practice and research. The main objective of this thesis was to evaluate the applicability of sustained maximal inspiratory pressure test (SMIP) as evaluation of the inspiratory muscle function, and the Glittre activities of daily living test (TGlittre) to assess the functional capacity. Participants with normal pulmonary function performed two functional tests (incremental shuttle walk test (ISWT) and TGlittre) with expired gases analysis, and three inspiratory muscle function tests (maximal inspiratory pressure (MIP), SMIP and endurance). The results were presented in three papers. The first study aimed to evaluate the relationship between the area under the pressure-time curve (AREA_SMIP), derived from SMIP test and the inspiratory muscle work (Work_insp) derived from inspiratory endurance test. The secondary objective was to assess the participants' perception regarding these tests. The results showed that the variable AREA_SMIP provides 78% of the Work_insp (r=0.88; p<0.0001; power=0.99). Regarding the participants’ perception, 86.7% reported low or no fatigue to perform SMIP and 53.3% to perform the inspiratory muscle endurance test. The aim of the second study was to characterize the aerobic metabolic demand at steady state oxygen consumption (VO2) of the TGlittre, and evaluate the induced physiological responses. The results showed that the mean time spent to performed the TGlittre was 145.86 seconds (CI 95%: 134.39-157.32), of these, 74.68 seconds (CI 95%: 69.20-80.15) were necessary to reach the steady state. The VO2 to perform the test corresponded to 61.6% of the maximum predicted, heart rate (HR) reached represented 71.5% of maximal HR predicted, and the ventilation was equivalent to 27.4% of ventilatory reserve. The last study was developed to evaluate and compare the cardiovascular, ventilatory and metabolic responses of the ISWT and TGlittre. Cardiorespiratory, ventilatory and metabolic variables at ISWT were higher than TGlittre. VO2_TGlittre was 22.2 ± 4.6 vs 27.8 ± 5.3 mL•kg-1•min-1 (p <0.001) from VO2_ISWT, and the HR reached on TGlittre was 135 ± 19 vs 161 ± 18 bpm on ISWT (p<0.001). The correlations between time spent in TGlittre and the distance walked in ISWT (r=-0.54; p=0.003), the average VO2_TGlittre and peak VO2_ISWT (r=0.82; p<0.0001) and HR achieved on the TGlittre and on the ISWT (r=0.85; p<0.0001) were moderate to high. Therefore, from results of these studies it is possible to conclude: (1) AREA_SMIP is able to estimate on the Work_insp developed in inspiratory muscle endurance test, as an alternative option to evaluate the inspiratory muscle function; (2) TGlittre is a submaximal test that maintains a steady state, which the average metabolic expenditure is equivalent to moderate intensity activities; (3) TGlittre and ISWT, are complementary to evaluate the functional capacity, TGlittre provides information on functional performance and ISWT provides information about the responses to exercise in a wide range, by different levels of the test.